Clinical maxillary sinus elevation surgery - Kao, Daniel W. (Ames, Iowa : John Wiley & Sons Inc., 2014)
Maxillary sinus elevation, followed by placement of a wide variety of grafting materials, has been the generally accepted surgical protocol for the development of bone in the sinus cavity. Over the years, various techniques have been proposed for maxillary sinus elevation, which differ in surgical approach, bone graft materials, and advanced technology application for hard tissue and soft tissue management. Dr. Kao and a team of experts begin by discussing anatomy, radiographic image applications and limitations, and then provide step-by-step clinical procedures for the lateral window techniqu.
Anatomy and physiology of the maxillary sinus -- The applications and limitations of traditional x-ray images -- The applications and limitations of advanced (three-dimensional) radiographic imaging techniques -- Conventional instruments preparation and pre-clinical training of lateral window technique -- Clinical procedures of lateral window technique -- Avoiding and managing complications for the lateral window technique -- Advanced techniques of lateral window technique -- Basic instruments and materials of trans-alveolar approach : osteotome technique -- Clinical procedures of trans-alveolar osteotome approach -- Post-operation management of the trans-alveolar osteotome approach -- Advanced techniques of trans-alveolar approach -- Decision tree for the maxillary sinus elevation options -- Choices of bone grafts materials -- Review of dental implant success and survival rates.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Maxillary Sinus -- surgery; Maxillary Sinus -- surgery; Dental Implants; Maxillary Sinus -- pathology; Oral Surgical Procedures, Preprosthetic -- methods; Osteotomy -- methods; Sinus Floor Augmentation -- methods; Electronic books